Analisis dan Simulasi Model Matematika SIRC pada Dinamika Penyakit Diabetes Mellitus dengan Komplikasi - Awawin Mustana Rohmah; Alvina Wiliyanti; Mohammad Syaiful Pradana; Siti Alfiatur Rohmaniah; Rifky Ardhana Kisno Saputra (UJMC (Unisda Journal of Mathematics and Computer Science), 2025)
Diabetes is a global health problem with a continuously increasing prevalence, adversely affecting quality of life and increasing the risk of health complications. This study applies the SIRC mathematical model to describe the temporal dynamics of diabetes, with model parameters calibrated using recent data. System stability is analyzed using the Jacobian method to determine equilibrium points and system behavior. The results indicate a high incidence of disease and complications, while the recovery rate remains relatively low. The basic reproduction number (R₀) of 1.6483 suggests that the disease still has the potential to spread. Furthermore, the equilibrium point E₁ is found to be unstable due to the presence of positive eigenvalues. This study provides important insights into diabetes dynamics that may support effective health management strategies.